ISSUES OF MAINTENANCE OF NATIONAL AND CULTURAL IDENTITY AT THE STAGE OF DEVELOPMENT OF MODERN KAZAKHSTANI SOCIETY (Аль-Фараби, 2023)
Since the last century, the formation and stabilization of national identity has been one of the main topics of theoretical and empirical research in the social sciences. The urgency of this issue has become even more relevant in the context of globalization, which violates the national cultural, economic and political boundaries. In this regard, the establishment of national and cultural identity in modern Kazakhstan society is one of the most important issues. The scientific article is devoted to the preservation of national and cultural identity at the stage of development of modern Kazakhstan society. In the process of development of independent Kazakhstan, economic, socio-political stability, religious tolerance, state security are important values for our society. For ethos, social groups, a large-scale issue for a person is cultural identity, because each subject of culture seeks to realize its potential in social and cultural interaction with subjects of other cultures. Here, each of them, along with cultural innovation, strives to preserve and further develop their cultural traditions and values. Therefore, this article provides a scientific and theoretical analysis of the formation and preservation of Kazakhstan's identity in the development of the country, identifies and formulates the goals of these processes.Key words: Identity, national culture, traditions, society, revival, values.